Suluk “Sigra Bala Kang Tumingal”: Sumber Inspirasi Nilai Kehidupan Dalam Meningkatkan Pendidikan Karakter Bagi Siswa SMPN 3 Grogol - Rista , Diana; Hanggara, Guruh Sukma; Sasmita, Wikan (PT. Kreasi Karya Majakata, 2024)
SMPN 3 Grogol, known as Simpatig Budaya, is a school rich in cultural diversity and committed to preserving local cultural heritage, including wayang art. This research focuses on the suluk